Thermal Transport Characteristics of Fractional Maxwell Fluid Model for Blood Flow in a Stenosed Artery - Ali Musa; A. M Kwami; A. G Madaki (Darul Yasin Al Sys, 2026)
This study examines the unsteady heat transfer behavior of fractional Maxwell nanofluid blood flow in a stenosed artery under the combined effects of a magnetic field, thermal radiation, viscous dissipation, and internal heat generation. The study aims to provide a more realistic representation of thermal transport in pathological blood flow by incorporating fractional-order viscoelastic effects. The governing fractional energy equation is solved using a semi-analytical Laplace transform approach, while numerical inversion is carried out through the Concentrated Matrix-Exponential method. The results show excellent agreement with existing studies, confirming the validity of the proposed approach. The findings further reveal that thermal radiation, magnetic field strength, viscous dissipation, fractional order, and relaxation time increase temperature distribution, whereas higher Reynolds and Prandtl numbers reduce it. The study concludes that fractional-order modeling offers a more realistic and effective framework for analyzing thermal transport in stenosed arterial blood flow, thereby contributing to improved understanding of heat transfer behavior in pathological hemodynamic conditions.